2016
DOI: 10.3390/su8070646
|View full text |Cite
|
Sign up to set email alerts
|

Multicriteria Decision Analysis to Develop Effective Sustainable Development Strategies for Enhancing Competitive Advantages: Case of the TFT-LCD Industry in Taiwan

Abstract: Abstract:In the Internet of Things era, panel displays play a major role in human life, because humans frequently use liquid crystal displays to monitor their electrical devices. The display industry creates remarkable economic output, but every manufacturing process inevitably has some undesirable effects on the environment. With the increasing awareness of environmental protection, balanced development is necessary to address the emerging market trends. However, short-sighted manufacturing corporations that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 83 publications
(204 reference statements)
4
50
1
1
Order By: Relevance
“…In fact, the greatest difference between the two methodologies is that ANP is applied to decision-making problems for interrelationships in outer dimensions, whereas the AHP assumes the independence of outer and inner dimensions. As Lu et al [40] claim, the outcome of the decisions may be influenced if there exists a significant interrelationship between dimensions and criteria that is not considered. On the other hand, ANP allows for a representation of decision-making in a complex environment with a network structure rather than with a hierarchical structure [40,42].…”
Section: Analytic Network Processmentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the greatest difference between the two methodologies is that ANP is applied to decision-making problems for interrelationships in outer dimensions, whereas the AHP assumes the independence of outer and inner dimensions. As Lu et al [40] claim, the outcome of the decisions may be influenced if there exists a significant interrelationship between dimensions and criteria that is not considered. On the other hand, ANP allows for a representation of decision-making in a complex environment with a network structure rather than with a hierarchical structure [40,42].…”
Section: Analytic Network Processmentioning
confidence: 99%
“…Therefore, the DEMATEL method can be used to solve the inter-dependence and feedback of criteria in the real world; (b) The traditional MCDM methods provide the relative best solution from the fixed set ("max-min" as target) of alternatives to use for ranking and selection, but generally, the real-world problems are assessed by achieving the aspiration levels ("aspiration-worst" as target). The modified MCDM have replaced the traditional MCDM methods as modified VIKOR [40,141,145,146], modified GRA (grey relation analysis) [147], modified PROMETHEE [147] and so on, to obtain the desirable value (aspiration level); (c) MADM methods and tools should be used to compare alternatives and goals or aspiration levels of the criteria, but also, as an improvement, MADM methods can only conduct a single alternative evaluation for building the best improvement strategy plan towards continuous improvement and sustainability to achieve the aspiration level [40,141] and not only in ranking and selection; (d) The traditional aggregation function model in MADM methods should be changed, including a non-additive (super-additive) approach for solving real-world problems [144,148]; even fuzzy logic [47,144] can also be used to aggregate the values of multiple attributes in a non-additive approach.…”
Section: New Concepts and Trends Of Mcdmmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it may affect the outcome of decision-making if we do not take the influence interrelationship among dimensions and criteria into account. Therefore, in this study, we identified the mutual IWs of DANP among the criteria based on the basic concept of ANP to solve these problems [89][90][91]. This approach is more suitable for solving realworld applications.…”
Section: Obtaining the Influential Weights Of Criteria And Dimensionsmentioning
confidence: 99%